PERBEDAAN KADAR CO DI UDARA BADAN JALAN BERDASARKAN KERAPATAN TANAMAN PENGHIJAUAN DI KOTA SEMARANG TAHUN 2OO3 - Atik . Susanti; M. . Sulchan; Mifbakhuddin . . (Universitas Muhammadiyah Semarang, 2004)
ABSTRACT Background : Carbon monoxide (CO) is the most pollutant substance as the result of incomplete combustion from the carbon contained material ft'om fuel or other materials. Motor vehicles are the biggest contributor for air pollution. It is caused by smoke from various kinds of vehicles , which produce many dangerous pollution gasses such as Carbon monoxide (CO) and hydrocarbon (Hc). Air pollution level caused by vehicle gas emition in Semarang is believed to be at the dangerous level for the people's health. According to Bapedal (96), Semarang has been categorized as the third most polluted city after Jakarta and Bandung. The preventive action to overcome this problem is by planting trees or plants. Plant can be selected from trees along the streets because it can clean the air from contaminant and also it can function as green belt. Objective : in order to know the CO level along the street based on the interval distance between plants in Semarang in rhe year of 2003. Method : This explanatory research is using the cross sectional approach. The sample in this research is comparing the quality of the air between two major streets in Semarang. The first, it is taken from the air in Jalan Teuku Umar , which have a closer distance between its plants and the other is taken from Jalan Majapahit which has a scarce plants. Both streets have the same average rate of vehicles.The independent variabel is the closed or unclosed green plants, whereas the dependent variabel is the CO disposal. The controled variabel is the total number of vehicles This research was conducted in June 2aB, and the data were gathered from observation, direct measuring and laboratory test. Stastical analysis was undertaken using t test. Result : The average CO in Teuku Jmar street is 781,2500 pgr/m3, whereas in Majapahit 1354,1675 pgrlm3 The test has found the significant result of p = 0,011, it means p< q0,05, so there are some differences for CO disposal based on the distance of its plant. Conclusion : There are some dffirences for CO disposal based on the distance of plants on the street. Keywords : CO disposal, green plant",